2021
DOI: 10.4103/ijsp.ijsp_151_20
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Wives of Persons with Alcohol Use Disorder and their Marital Quality

Abstract: Context: Alcohol use disorder (AUD) in men has a profound impact on the mental health of wives of persons with alcohol use disorder (WoPA). Quality of their marital life is an overlooked aspect which affects both the mental health of the partners and their children. Resilience in WoPA acts as a protective element in maintaining their marital quality and, in turn, their mental health. Aims: The aim of this study was to assess the resilience in the WoPA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…Wife battering is another consequence of spouse addiction. Johnson et al reported that substance abuse is one of the main reason for wife battering (22). Similar results of physical abuse were reported by researchers (23).…”
Section: Discussionsupporting
confidence: 61%
“…Wife battering is another consequence of spouse addiction. Johnson et al reported that substance abuse is one of the main reason for wife battering (22). Similar results of physical abuse were reported by researchers (23).…”
Section: Discussionsupporting
confidence: 61%
“…The study suggests various strategies to improve the quality of life for wives of individuals with AUD, such as facilitating access to support groups, community engagement programs, and resources for personal growth [ 25 - 27 ]. These interventions, as highlighted by participants, directly link resilience to the welfare of children, further underlining the importance of supporting the non-AUD husband in their parenting role [ 28 , 29 ]. This approach aims to strengthen family resilience, offering a pathway to better family outcomes irrespective of their socio-economic backgrounds.…”
Section: Discussionmentioning
confidence: 99%